Effects of energy and amino acid intake during gestation on reproductive performance, milk composition, antioxidant status and placental nutrient transport in high-parity sows - Hu, Liang; Zheng, Jie; Wu, Fali; Fang, Zhengfeng; Che, Lianqiang; Wu, De (Frontiers in Veterinary Science, 2025)
Appropriate nutritional strategies show promise for enhancing productive performance and longevity of sows. This study aimed to determine the effects of increased energy and amino acids (AA) intake during gestation on reproductive performance, milk composition, blood parameters, placental nutrient transport and antioxidant capacity of high-parity sows. A total of 72 Landrace × Yorkshire sows (seventh to ninth parity) were randomly assigned to dietary treatments consisting of combinations of 2 energy levels and 2 AA levels in a 2 × 2 factorial design. Blood and milk samples and placentas from sows were collected to measure biochemistry parameters, milk composition, antioxidant indexes, and indicators related to nutrient transport. The results showed that sows fed high energy reduced the number of live born piglets (p < 0.05), increased the birth weight of piglets (p < 0.05). Further observation showed that sows fed high energy decreased plasma progesterone at 30 and 60 days of gestation and plasma glutathione peroxidase (GPX) and total superoxide dismutase (T-SOD) at 90 days of gestation (p < 0.05), increased fat content in colostrum and average daily weight gain of piglets during lactation (p < 0.05). Moreover, high energy intake during gestation decreased mRNA expression of GPX and increased mRNA expression of glucose transporter 3 in the placenta (p < 0.05). High AA intake during gestation showed a tendency to increase litter birth weight and colostrum protein content (p < 0.10), and increased plasma urea nitrogen at day 110 of gestation and plasma T-SOD at day 90 of gestation (p < 0.05). Furthermore, sows fed high AA intake during gestation increased mRNA expressions of placental extracellular SOD and sodium-dependent neutral amino acid transporter 1 (p < 0.05). In conclusion, sows feed high energy during gestation negatively impacted fetal survival by reducing progesterone concentrations and antioxidant capacity, while simultaneously increasing piglet birth weight through enhanced placental nutrient transport. Moreover, sows received high AA during gestation exhibited better redox status and improved litter performance, which can be attributed to enhancements in antioxidant capacity and colostrum composition.